A new type of biomarker for heat stress: insights from immunology - Ye, Chunmei; Zhang, Zhipeng; Yang, Zhangping (Frontiers in Immunology, 2026)
Global warming exacerbates heat stress in dairy cows, while traditional indicators like the Temperature-Humidity Index (THI) struggle to accurately reflect individual physiological response variations. This review systematically analyzes the dynamic changes in the bovine immune system under heat stress and proposes immune-related biomarkers as a novel strategy for early warning and individualized assessment. Research reveals that heat stress compromises the innate immune barrier function of cows, suppressing neutrophil chemotaxis and antimicrobial peptide synthesis, leading to a decline in the opsonophagocytic index and endotoxin translocation. Expression of intestinal tight junction proteins (e.g., Claudin-1, Occludin) is significantly downregulated (by ~40%), causing endotoxin translocation (serum LPS increases ~3-fold) and disruption of the blood-milk barrier, increasing mastitis risk by 2–3 times. Regarding adaptive immunity, the proliferation and differentiation of T/B cells are impaired, the CD4+/CD8+ T cell ratio decreases, antibody affinity maturation is suppressed, and the efficiency of immune memory formation post-vaccination is reduced. Concerning mammary immunity, the number of viable granulocytes in milk decreases, mammary epithelial cells increase, pro-inflammatory cytokine levels rise, and the risk of clinical mastitis increases 2–3 fold. Furthermore, heat stress induces metabolic reprogramming, gut microbiota dysbiosis, oxidative stress, and activation of the hypothalamic-pituitary-adrenal (HPA) axis. Novel biomarkers, such as Heat Shock Proteins (HSPs), Neutrophil-to-Lymphocyte Ratio (NLR), cytokine profiles (e.g., IL-6/TNF-α), acute-phase proteins (e.g., Haptoglobin, Hp), and epigenetic markers, provide crucial targets for heat-tolerant breeding and early intervention, promising to enhance the climate resilience of the dairy industry.